PECULIARITIES OF TEACHING CHILDREN WITH HEARING IMPAIRMENT IN INCLUSIVE AND SPECIALIZED EDUCATIONAL INSTITUTIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article discusses the advantages of inclusive education, as well as its financial aspects in comparison with specialized educational institutions for children with special educational needs.